A method using uniform yellowing pigmentation to model the color perception of the elderly people - Hassan, Mohd Fikree; Paramesran, Raveendran; Tanaka, Yoshiki; Tanaka, Kiyoshi (Springer Verlag, 2018)
As the usage of color images in presenting information via Web sites and smartphone applications increases, the color perception loss may affect the accuracy of the information when it is presented to elderly people. The earlier study considered non-uniform yellowing pigmentation model to mimic the color perception loss of elderly people. Recently, two clinical studies have shown that uniform yellowing pigmentation occurs on the human crystalline lens. In this paper, we propose a mathematical model using uniform yellowing pigmentation to mimic the color perception experienced by elderly people. The uniform yellowing pigmentation is formed using the measured transmittance functions of the LCD display and the spectral transmission factor. The uniform yellowing pigmentation formed is in agreement with the results of the clinical studies. Moreover, subjective evaluation showed that the results from the proposed method are closer to the clinical data and showed improvement when compared to the results from the non-uniform yellowing pigmentation method.